3D structure of NT-3 Protein (Neurotropin 3) of Pigeon (Columba livia) using Server-Swiss Model - Zarkiyani, Tina; Budiarsa, I Made; Astija, Astija; Bialangi, Mursito S (Universitas Tanjungpura, 2021)
The NT-3 protein plays an important role in the development and differentiation of neurons, and is unique in the neurotropin family, that it can bind to 3 Trk receptors, namely TrkC, TrkA and TrkB. This study aimed to analyze the characteristics and three-dimensional structure of NT-3 protein in Columba livia. The target protein was obtained from Uniprot server with the access code of PKK30025.1 using template 3buk.1A (PDB-ID) analyzed in-silico through homology method using SWISS-MODEL server. The results showed that the three-dimensional structure of the target NT-3 protein with a template formed a β-sheet and loop structure, which was composed of 304 amino acids, with the highest amino acid composition was serine at 8.88 mol polar, and the lowest amino acid was tryptophan at 1.32. moles which was relatively nonpolar. The analysis results of the structural quality revealed an identity value of 98.20%, QMEAN of 0.8, QMQE of 0.25, and the analysis on the Ramachandran plot presented an outlier value of 0.92%; the most favored region value was 94.5%, with good structural quality. The results of the 3-dimensional structure of the NT-3 Columba livia protein are expected to be useful for further research to determine the active side and interactions of proteins in carrying out their functions.